Titanocene modulation of cytokine imbalance induced by Ehrlich ascites tumour progression - Valadares, M. C.; Klein, Stanlei Ivair [UNESP]; Queiroz, MLS (Elsevier B.V., 2004)
In the present work, we have studied the effects of two titanocenes, biscyclopentadienyldichlorotitanium IV (DDCT) and its derivative, biscyclopentadienylditiocianatetitanium IV (BCDT), on the production of cytokines [interferon-gamma (IFN-gamma), interelukin-1, interleukin (IL) 2, IL-4, and IL-10] by concanavalin A (Con A)-stimulated T cells obtained from Ehrlich ascites tumour (EAT)-bearing BALB/c mice. The treatment consisted of intraperitoneal (i.p) administration of 15 mg/kg/day DDCT for 2 days or 10 mg/kg/day BCDT for 3 days. We observed that the levels of IFN-gamma, but not IL-2, were dramatically increased in the early phase of EAT development. With tumour evolution, however, a sharp and progressive decrease in the levels of both IFN-gamma and IL-2 was found concomitantly to an enhancement in the levels of IL-10. Treatment of these mice with both titanocene compounds demonstrated that DDCT is more effective in modulating the cytokine imbalance induced by the tumour since it could prevent the early enhancement of IFN-gamma, the late decline of IFN-gamma and IL-2, and the increase in the IL-10. The administration of BCDT, in spite of preventing early IFN-gamma enhancement and increase in IL-10, did not produce any change in the IL-2 levels and did not prevent the decline of IFN-gamma levels during tumour evolution. Collectively, these results reveal that the ability of titanocenes to reverse tumour-induced immunosuppression and delay tumour growth is more evident in the DDCT compound, thus indicating that the substitution of the halides halogens by pseudohalogens, present in the molecular structure of BCDT, leads to a less effective antitumoral compound. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: titanocene; cytokine; Ehrlich ascites